Resource Management Practices and Operational Performance of Coffee Shops: Basis for Action Plan - Asuncion, Rammel Albertoni L.; Bucal, Remedios J.; Pendon III, Fernando T. (International Journal of Research in Interdisciplinary Studies, 2025)
This study investigates the relationship between resource management practices and operational performance in micro and small coffee shops within the province of Laguna, Philippines. The research focuses on four key areas of resource management: physical, human, financial, and service, and evaluates their impact on three aspects of operational performance—service efficiency, product quality, and customer satisfaction. Utilizing a descriptive-correlational research design, the study surveyed 74 coffee shop owners and managers using a validated questionnaire. The data were analyzed using statistical tools such as weighted mean, Pearson’s correlation, and MANOVA to assess both the relationship and differences between variables when grouped by business profile. Findings revealed that most coffee shops in Laguna moderately practice resource management strategies, with service efficiency and customer satisfaction rated as good. Significant relationships were found between effective resource management and higher levels of operational performance. Moreover, the results showed notable differences in resource and operational performance based on location, years of operation, and capital investment. The study underscores the importance of strategic resource allocation, workforce development, and financial planning in enhancing business outcomes. An action plan was proposed to guide coffee shop owners in scaling operations and improving sustainability. This research provides valuable insights for entrepreneurs, managers, consultants, and investors in the food and beverage industry seeking to strengthen business practices and foster long-term success.